Transforming pharmacy education: Societal and professional challenges - Tasić Ljiljana; Parojčić Jelena; Krajnović Dušanka (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2015)
Pharmacy profession has undergone through a period of intensive review and redefining of its professional roles, practice, and educational needs. Pharmacy graduates are now expected to be equipped with specific competencies necessary for provision of patient-centered and population-based pharmaceutical care, responsible use of medicines and management of limited healthcare resources. In line with other health professionals' education, pharmacy education progresses through several 'generations' of reforms which are faced with different professional and societal challenges. Thus, they have been implemented differently and to different extent in various regions. The aim of this communication is to point out the critical factors for further advancement of pharmacy education, with the emphasis on relevant societal and professional challenges in Serbia. Contemporary health professionals' education in developed countries is based on the four main paradigm including: (I) integrated interdisciplinary competency-based curriculum, (II) active learning approach involving clinical experience and interprofessional teaching and learning, (III) commitment to serve the community health needs and (IV) continuous teaching competencies development of academic staff and teacher practitioners in order to accommodate these innovations. The majority of developing countries, including Serbia, are in the initial phase of these reforms. Lack of integrated policy for healthcare and education system development, insufficient capacity of the professional regulatory bodies, and lack of motivation and commitment to change in the academic community were identified as major obstacles to progress.